ANALISIS DERAJAT KESEHATAN MASYARAKAT DI KABUPATEN PADANG PARIAMAN MENGGUNAKAN METODE STUCTURAL EQUATION MODELLING (SEM-PLS) - cahayani, erika putri; Novio, Rery (JURNAL BUANA, 2024)
his Research was conducted to analyze and describe the condion of health status in Padang Pariaman Regency so that later it can be used as reference material in improving development in the health sector. The method in this study uses the Structural Equation Modelling with the Partial Least Square model. Data collection is carried out using secondary data, namely data that is already available at the Health Officeand the Health Office and the Central Bureau os Statistics for Padang Pariaman Regency in 2021, then processed using SmartPLS software. The results showed that the Environment and Health services had a significant positive effect on Health Statuswith an Effect Size value of more than >0,15 which means (moderate effect), while Health Behavior had a significant negative effect on Health Status with an Effect Size value of 0,02 which means (small effect).